Genetic Testing and Counselling in Hypertrophic Cardiomyopathy Frequently Asked Questions - Girolami Francesca; Gozzini Alessia; Pálinkás Eszter Dalma; Ballerini Adelaide; Tomberli Alessia; Baldini Katia; Marchi Alberto; Zampieri Mattia; Passantino Silvia; Porcedda Giulio; Calabri Giovanni Battista; Bennati Elena; et al. (2023)
Genetic counselling and genetic testing in hypertrophic cardiomyopathy (HCM) represent an integral part of the diagnostic algorithm to confirm the diagnosis, distinguish it from phenocopies, and suggest tailored therapeutic intervention strategies. Additionally, they enable cascade genetic testing in the family. With the implementation of Next Generation Sequencing technologies (NGS), the interpretation of genetic data has become more complex. In this regard, cardiologists play a central role, aiding geneticists to correctly evaluate the pathogenicity of the identified genetic alterations. In the ideal setting, geneticists and cardiologists must work side by side to diagnose HCM as well as convey the correct information to patients in response to their many questions and concerns. After a brief overview of the role of genetics in the diagnosis of HCM, we present and discuss the frequently asked questions by HCM patients throughout our 20-year genetic counselling experience. Appropriate communication between the team and the families is key to the goal of delivering the full potential of genetic testing to our patients.
Keywords: Klinikai orvostan